2018
DOI: 10.1590/s1980-220x2017027903425
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes of nursing students towards substance users and perceptions about religious/spiritual care

Abstract: Objective: To evaluate the impact of an educational intervention on the attitudes of Nursing students towards users of psychoactive substances (excluding alcohol and tobacco) and their perceptions about the religious and spiritual care offered within the health services. Method: Quasi-experimental study. We applied a questionnaire before and one month after an intervention about the comprehensive care of substance users, containing: sociodemographic information, knowledge, the Treatment Spirituality/Religiosit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 28 publications
0
5
0
3
Order By: Relevance
“…And nursing students with higher spiritual care perceptions are more expressive through spiritual care in nursing practice, so as to achieve inner resonance and empathy with patients, increase the accuracy and effectiveness of clinical communication, and it can also promote the nurse–patient communication. It is conducive to meeting the needs of patients and their families and relieving their anxiety, and promoting the establishment and development of a good nurse–patient relationship, thereby improving the quality of care and satisfaction (Chen et al, 2018; Goncalves et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…And nursing students with higher spiritual care perceptions are more expressive through spiritual care in nursing practice, so as to achieve inner resonance and empathy with patients, increase the accuracy and effectiveness of clinical communication, and it can also promote the nurse–patient communication. It is conducive to meeting the needs of patients and their families and relieving their anxiety, and promoting the establishment and development of a good nurse–patient relationship, thereby improving the quality of care and satisfaction (Chen et al, 2018; Goncalves et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…And research by Kalkim et al (2018) showed that spiritual care perceptions of nursing students were affected by many factors such as religious beliefs, and educational level, and was generally not high, and it was positively correlated with its spiritual care competence. Nursing students' spiritual care perceptions may be also closely related to their spiritual well-being and competence of providing spiritual care for patients (Goncalves et al, 2018). However, their understanding of the connotation of spiritual care is not deep and thorough enough, their practical competence is low, and clinical practice effect is poor, which may be related to the inadequacy of spiritual care education in universities and colleges around the world.…”
Section: Introductionmentioning
confidence: 99%
“…Among instruments used to measure attitudes in the Brazilian context, are the Drug and Drug Problems Perceptions Questionnaire (DDPPQ-br) and the Short Alcohol and Alcohol Problems Perception Questionnaire (SAAPPQ). The DDPPQ-br assesses attitudes towards drug users and the SAAPPQ assesses attitudes in relation to alcohol users (20) . Both were tested and validated in a sample of Nursing students and are originated and based on the same theoretical reference of the Alcohol and Alcohol Problems Perceptions Questionnaire (AAPPQ).…”
Section: Introductionmentioning
confidence: 99%
“…A formação de profissionais de saúde, especialmente os enfermeiros, é essencial para a detecção precoce dos consumos de risco de álcool; implementar as Intervenções Breves na redução de consumo excessivo de álcool, monitorização e encaminhamento, deve, portanto, ser uma prioridade durante o processo de formação profissional (6) . É necessário valorizar aspectos da formação em enfermagem, não se limitando apenas aos conhecimentos técnicos, mas enaltecer os recursos existentes para um cuidado integral, com implicações positivas na assistência às pessoas que consomem álcool e outras drogas de forma abusiva (7) . Desta via, percebe-se a relevância da aplicação das IBs nos cuidados primários de saúde, sendo os enfermeiros peças fundamentais no processo da detecção precoce de utentes com padrões de risco/nocivo em relação ao uso de álcool e a aplicação das IBs de acordo com o nível de risco encontrado (8) .…”
Section: Introductionunclassified